The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/solr.202100872
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5‐Triphenylbenzene Based Porous Conjugated Polymers for Highly Efficient Photoreduction of Low‐Concentration CO2 in the Gas‐Phase System

Abstract: Herein, three 1,3,5‐triphenylbenzene based porous conjugated polymers (PCPs) are designed for photochemical reduction of CO2 in simulated flue gas in the mild gas−solid reaction system. By tuning the nature of the comonomers, the PCPs present high surface areas, high CO2/N2 selectivity, and broad visible light absorptions with bandgaps of 1.81−2.07 eV. At 1 bar and 273 K, the CO2 uptake capacity of PCPs is enhanced from 1.28 to 2.18 mmol g−1, with an increase in CO2 adsorption heat from 21.8 to 28.3 KJ mol−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The characteristic peak at 90 ppm originated from alkyne carbons (C≡C) owning to the efficient coupling of the comonomers as indicated in our previous studies. [25] This can be further confirmed by FT-IR spectra, the stretching vibration of the C≡C could be observed around 2195 cm À1 . For P2 and P3, the peaks at 190.69 and 180.05 ppm in NMR spectra were accountable for the keto group (C═O) in the polymer backbone.…”
Section: Synthesis and Characterizationmentioning
confidence: 56%
See 2 more Smart Citations
“…The characteristic peak at 90 ppm originated from alkyne carbons (C≡C) owning to the efficient coupling of the comonomers as indicated in our previous studies. [25] This can be further confirmed by FT-IR spectra, the stretching vibration of the C≡C could be observed around 2195 cm À1 . For P2 and P3, the peaks at 190.69 and 180.05 ppm in NMR spectra were accountable for the keto group (C═O) in the polymer backbone.…”
Section: Synthesis and Characterizationmentioning
confidence: 56%
“…As reported in our previous studies, inductively coupled plasma-mass spectrometry (ICP-MS) analysis indicated the presence of 0.31-0.40 wt% Pd and 0.012-0.042 wt% Cu in the porous polymer due to residual catalyst. [19,25] The formation of polymer networks was verified by cross-polarization/magic angle spinning (CP/MAS) 13 C NMR spectra and Fourier transform infrared (FT-IR) spectra (Figure S2-S5, Supporting Information). The 13 C NMR spectra showed peaks at approximately 120-140 ppm for all polymers, which could be assigned to sp 2 hybridized carbons.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic functionalities pyrene, [3] triazine, [4] benzothiadiazole, [4] cyclotriphosphazene, [5–6] triphenylamine, [7] oxadiazole, [7] eosin Y, [8] carbazole, [9] naphthalenedimide, [10–11] fluorene [10] phenanthraquinone, [12] and 1,3,5‐triphenylbenzene [13] have been used to build cross‐linked or linear conjugated polymer catalysts (Scheme S1, Supporting Information). Among these polymeric photocatalysts, a pyrene‐based polymer gave a CO product rate ( R CO ) of 47.37 μmol g cat −1 (per gram of catalyst) h −1 (per hour), [3] and an N,O,P‐containing polymer afforded a CH 4 production rate ( R CH4 ) of 22.5 μmol g cat −1 h −1 [5] .…”
Section: Introductionmentioning
confidence: 99%
“…It is electron-rich with two sulfur heteroatoms and flat and has remarkable optic/electronic and electrochemical oxidation/reduction properties. Another important building block is 1,3,5-triphenylbenzene (TPB), which is a photochemically and thermally stable chromophore with a π-extended structure. As in TTs, TPB has a useful core for various electronic areas such as OLED, water splitting, triplet–triplet annihilation photon upconversion, and CO 2 photoreduction. Since addition of sulfur has a positive impact in catalyzing the ORR, combining a porous structure with a thiophene-based backbone may help to enhance the ORR activity.…”
Section: Introductionmentioning
confidence: 99%